Effects of cold water immersion on the recovery of physical performance and muscle damage following a one-off soccer match - Ascensão, A.; Leite, M.; Rebelo, A. N.; Magalhaes, S.; Magalhaes, J. (Journal of Sports Sciences, 2011)
The aim of this study was to assess the effects of a single session of cold or thermoneutral water immersion after a one-off match on muscular dysfunction and damage in soccer players. Twenty-male soccer players completed one match and were randomly divided into cryotherapy (10 min cold water immersion, 10°C, n = 10) and thermoneutral (10 min thermoneutral water immersion, 35°C, n = 10) groups. Muscle damage (creatine kinase, myoglobin), inflammation (C-reactive protein), neuromuscular function (jump and sprint abilities and maximal isometric quadriceps strength), and delayed-onset muscle soreness were evaluated before, within 30 min of the end, and 24 and 48 h after the match. After the match, the players in both groups showed increased plasma creatine kinase activity (30 min, 24 h, 48 h), myoglobin (30 min) and C-reactive protein (30 min, 24 h) concentrations. Peak jump ability and maximal strength were decreased and delayed-onset muscle soreness increased in both groups. However, differential alterations were observed between thermoneutral water and cold water immersion groups in creatine kinase (30 min, 24 h, 48 h), myoglobin (30 min), C-reactive protein (30 min, 24 h, 48 h), quadriceps strength (24 h), and quadriceps (24 h), calf (24 h) and adductor (30 min) delayed-onset muscle soreness. The results suggest that cold water immersion immediately after a one-off soccer match reduces muscle damage and discomfort, possibly contributing to a faster recovery of neuromuscular function.